Effectiveness of using brain-based learning theory in developing the achievement of 7th year female students in science - Al - Shaweesh, Juman Ghaleb Mohammed (Arab Journal for Sciences and Research Publishing, 2016)
This research aimed to know the effect of using brain-based learning theory in achievement to 7th year female students in science through proving the following hypotheses: -there is difference in the statistical sign at the sign level (0.01) between the average of the female students achievement marks in the experimental group who study according to brain-based learning theory and the average of the female students achievement marks in the control group who study according to the ordinary method The sample consists of (60)female students and they were in random allocation to two groups equally each of them of (30)female students from the experimental group which learnt according to ordinary method The research himself taught the two groups, and he made achievement test consisted of (20) item from multiple choice with four alternatives for each item The results showed the excellence of the experimental group to the controlling group in achievement The researcher submitted a number of recommendation and suggestions